Iterative and incremental developments: A brief history - Larman, Craig; Basili, Victor R. (Computer, 2003)
Although many view iterative and incremental development as a modern p ractice, its application dates as far back as the mid-1950s. Prominent software-engineering thought leaders from each succeeding decade supp orted IID practices, and many large projects used them successfully. T hese practices may have differed in their details, but all had a commo n theme-to avoid a single-pass sequential, document-driven, gated-step approach.
Keywords: Agile methods; Application software; Feedback; Government; History; Iterative and incremental developments; Iterative methods; Personnel; Programming; Radio access networks; Terminology; Testing; iterative enhancement; software engineering; software system